Using Improved Serial Blood Sampling Method of Mice to Study Pharmacokinetics and Drug–Drug Interaction. Issue 3 (1st December 2014) - Watanabe, Ayahisa; Watari, Ryosuke; Ogawa, Keiko; Shimizu, Ryosuke; Tanaka, Yukari; Takai, Nozomi; Nezasa, Ken‐Ichi; Yamaguchi, Yoshitaka
<x xml:space="preserve">Abstract</x> In pharmacokinetic evaluation of mice, using serial sampling methods rather than a terminal blood sampling method could reduce the number of animals needed and lead to more reliable data by excluding individual differences. In addition, using serial sampling methods can be valuable for evaluation of the drug–drug interaction (DDI) potential of drug candidates. In this study, we established an improved method for serially sampling the blood from one mouse by only one incision of the lateral tail vein, and investigated whether our method could be adapted to pharmacokinetic and DDI studies. After intravenous and oral administration of ibuprofen and fexofenadine (BCS class II and III), the plasma concentration and pharmacokinetic parameters were evaluated by our method and a terminal blood sampling method, with the result that both methods gave comparable results (ibuprofen: 63.8 ± 4.0% and 64.4%, fexofenadine: 6.5 ± 0.7% and 7.9%, respectively, in bioavailability). In addition, our method could be adapted to DDI study for cytochrome P450 and organic anion transporting polypeptide inhibition. These results demonstrate that our method can be useful for pharmacokinetic evaluation from the perspective of reliable data acquisition as well as easy handling and low stress to mice and improve the quality of pharmacokinetic and DDI studies. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:955–961, 2015